Prospective evaluation of the cost of diagnosis and treatment of invasive fungal disease in a cohort of adult haematology patients in the UK. (21st December 2014) - Ceesay, M. Mansour; Sadique, Zia; Harris, Ross; Ehrlich, Alice; Adams, Elisabeth J.; Pagliuca, Antonio
Abstract: Objectives: The direct cost of invasive fungal disease (IFD) includes antifungal drugs as well as diagnostic tests. The aim of this study was to determine these costs. Methods: A total of 203 haematology patients were enrolled into the study and followed for a median of 556 days. Data were prospectively collected on antifungal drugs, diagnostic tests, length of stay and antibiotic usage. Results: The overall mean (IQR) cost of care per patient (using UK-based reference costs) was £88 911 (45 339–121 594), £61 509 (39 748–78 383), £50 332 (23 037–72 057) and £34 075 (19 928–43 900) for proven/probable IFD, possible IFD, not classified and no evidence of IFD, respectively ( P < 0.001). The attributable cost of IFD was £54 836. Inpatient hospital stay accounted for nearly 74% of costs. In proven/probable IFD inpatient care, antifungals, antibiotics and IFD status accounted for 68%, 25%, 5% and 2%, respectively, compared with 85%, 11%, 2% and 2%, respectively, for no IFD ( P < 0.001). Among the allogeneic transplant patients, £36 914 (60%) of the total cost (£60 917) was used during the first 100 days. Conclusions: IFD was associated with longer length of stay and higher total overall cost of care, with attributable costs greater than £50 000 per case of IFD. Costs for inpatient stay far outstrip the cost of antifungal agents.